Characterization of the antioxidant, physicochemical and toxicological properties of an infusion of dehydrated Cordia lutea flower (Agroindustria, Sociedad y Ambiente, 2026)
The Cordia lutea flower contains a number of bioactive compounds of interest for beverage formulation. The objective of this study was to evaluate the antioxidant, physicochemical, and toxicological properties of an infusion of dehydrated Cordia lutea flower. A completely randomized design was used, and four different treatments were formulated (0.5 g, 1.0 g, 1.5 g, and 2.0 g of dehydrated Cordia lutea CLD). The heavy metal content of the CLD sample was evaluated, and the physicochemical properties, antioxidant activity, total phenols, and microbiological quality of the infusions were characterized using a Tukey test at the 0.05% significance level. The CLD showed low cadmium (
Keywords: Cordia lutea, antioxidants, flower, muyuyo